Compensation for Personal Injury in New Zealand - Its Rise and Fall - Atkin, W R (Victoria University of Wellington Law Review, 1997)
This article is a book review of Ian Campbell Compensation for Personal Injury in New Zealand: Its Rise and Fall (Auckland University Press, Auckland, 1996) 286 + x pages, $39.95. Atkin notes that New Zealand's accident compensation scheme was initially developed in a largely non-partisan way and was greeted positively. However, he notes that accident compensation has become a political football in recent years. Atkin thus recognises the timeliness of this book which provides the scheme's history and competing arguments for future change. Atkin concludes that the book's reference to the scheme's rise and fall is too pessimistic a picture, as the scheme continues to work well for many New Zealanders. However, Atkin notes that the book adds legitimate weight to the idea that accident compensation is under attack. Thus, with its grounding in the history of compensation mechanisms, the book is said to represent a valuable addition to the debate about future directions.